Service quality evaluation of international freight forwarders: An empirical research in East Asia - Sheng Teng Huang; Emrah Bulut; Okan Duru (Journal of Shipping and Trade (JST), 2019)
The purpose of this paper is to improve service quality of international freight forwarders and explore practical business solutions to enhance customer service level. Freight forwarder usually acts as an agent to source logistics service for shipper and work closely with carriers such as shipping line and airline companies. This business is characterized by lower capital investment and entry barrier comparing with carriers, and most of their major customers are small or medium size manufactures or traders. Providing high quality service to enhance customer satisfaction is the key mission since competition is extremely severe. This paper empirically investigates the leading freight forwarders to find important customer requirements in East Asian region such as Japan, Korea and Taiwan. Furthermore, the feature of the study by using quality function deployment approach would not only identify key technical measures but also explore meaningful business solutions as direction of quality improvement. The finding reveals key customer requirements are cheaper agency fees, door to door ability and instant response, and the key technical measures are customer relationship management, overall information system, service point and network. We would further discuss the empirical result and conclude managerial meaning for decision makers.
Keywords: 650; Quality function deployment; International freight forwarder; Shipping agent; Fuzzy analytic hierarchy process